PENGARUH GOOD CORPORATE GOVERNANCE, STRUKTUR KEPEMILIKAN DAN UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN YANG MENGIKUTI PROGRAM CORPORATE GOVERNANCE PERCEPTION INDEX DAN TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2010-2012 - Ahmad Hasan Deni Prakasiwi, 10.05.52.0133; Indarti, MG. Kentris (Students Journal of Accounting and Banking, 2014)
Implementation of good corporate governance (GCG) is needed to maintain public confidence in the consistency and a company. This study aims to examine and analyze the effect of good corporate governance, ownership structure and firm size on firm performance. The population in this study are all programs that follow the companys corporate governance index preception CGPI 2010-2012. Sampling technique is purposive sampling, sampling. Based on purposive sampling obtained a sample of 52 companies. Data analysis technique used is multiple linear regression analysis. Based on the test results it can be concluded that the positive effect of good corporate governance on firm performance (ROA). Good corporate governance can increase the confidence of investors to invest that will also have an impact on the companys performance improved. Managerial ownership structure negatively affect firm performance (ROA). The level of managerial ownership is too high agency problems due to conflicts of interest between managers and shareholders of the company will decrease the performance of the company. Firm size has no effect on firm performance (ROA). This means that the size of the companies had no effect on the level of performance of the company.Keywords: corporate governance, ownership structure, company size and company performance